2017
DOI: 10.1159/000450832
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Glucosamine Sulphate in Skin Ageing: Results from an ex vivo Anti-Ageing Model and a Clinical Trial

Abstract: Background: Glucosamine sulphate (GS) is essential in the biosynthesis of glycolipids, glycoproteins, glycosaminoglycans (GAGs), hyaluronate, and proteoglycans. Connective tissues primarily contain collagen and proteoglycans and play an important role in skin ageing. Objective: The objectives were to assess ex vivo the impact of GS on skin ageing parameters and in vivo the effect of GS on the skin physiology of mature healthy volunteers after oral intake. Methods: The impact of GS on skin ageing was assessed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…There is tantalizing evidence with established longevitypromoting medications, such as rapamycin, resveratrol, metformin, and others ( Figure 1B), and we provided experimental evidence for this with tretinoin, genistein, glucosamine, chondroitin, and hyaluronic acid ( Figure 5). Consistent with this is that glucosamine and chondroitin stimulate collagen synthesis in vitro and ex vivo of elderly human skin in a clinical trial (Gueniche and Castiel-Higounenc, 2017;Lippiello, 2007), extracellular matrix component hyaluronic acid treatments stimulate collagen synthesis in human photo-aged skin (Wang et al, 2007), and in mice (Fan et al, 2019), and topical application of rapamycin restores collagen VII levels in a clinical trial (NCT03103893) (Chung et al, 2019). ECM homeostasis might remodel or prevent glycation and crosslinking of collagens (Ewald, 2019).…”
Section: Discussionmentioning
confidence: 80%
“…There is tantalizing evidence with established longevitypromoting medications, such as rapamycin, resveratrol, metformin, and others ( Figure 1B), and we provided experimental evidence for this with tretinoin, genistein, glucosamine, chondroitin, and hyaluronic acid ( Figure 5). Consistent with this is that glucosamine and chondroitin stimulate collagen synthesis in vitro and ex vivo of elderly human skin in a clinical trial (Gueniche and Castiel-Higounenc, 2017;Lippiello, 2007), extracellular matrix component hyaluronic acid treatments stimulate collagen synthesis in human photo-aged skin (Wang et al, 2007), and in mice (Fan et al, 2019), and topical application of rapamycin restores collagen VII levels in a clinical trial (NCT03103893) (Chung et al, 2019). ECM homeostasis might remodel or prevent glycation and crosslinking of collagens (Ewald, 2019).…”
Section: Discussionmentioning
confidence: 80%
“…Fucose is the most popular hexose in the food industry (Shintani 2019). This monosaccharide is a component of sucrose and is highly sweet, leading to applications in the food and beverage industries with health bene ts due to low glycemic response (Gueniche and Castiel-Higounenc 2017). Our data showed that rice grains contain fucose with an average of 14 μg/mg (h b 2 = 0.97).…”
Section: Discussionmentioning
confidence: 73%
“…Again, the result was that the skin reaches biological maturity at an early age (15 -20 years) at which point it then starts to age [9]. Recent studies support the idea that collagen plays a role in the aging of the skin [10][11][12]. In addition to the work on the mechanical properties of the skin, investigations were also carried out in the past on the forces which were required to penetrate the skin and other materials with differently shaped objects.…”
Section: Discussionmentioning
confidence: 99%